On the Completeness and Minimality of Sets of Bessel Functions in Weighted \( L^2 \)-Spaces - Vynnyts’kyi, Bohdan V.; Khats’, Ruslan V. (Eurasian Mathematical Journal, 2015)
We establish a criterion for the completeness and minimality of the system \( (x^-p-1ρ_kJ_ u(xρ_k) : k N ) \) in the space \( L^2((0,1); x^2pdx) \), where \( J_ u \) is the Bessel function of the first kind of index \( u ≥ 1/2 \), \( p R \) and \( (ρ_k : k N) \) is a sequence of distinct nonzero complex numbers.